2009
DOI: 10.1007/s10661-009-1148-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment and decontamination of pesticides from meat under different culinary processes

Abstract: A total of 75 animals between 1.5 and 8 years old were randomly selected for the study. Of these, 57.8% were cross-bred animals and the rest were non-descript. Moreover, 61.8% of the animals under study were brought for slaughter from local sources and the rest from farm houses. Samples collected from five districts revealed contamination with traces of organochlorine pesticides (0.01-0.22 microg g(-1)) and organophosphorus pesticides (0.111-0.098 microg g(-1)). In general, all the raw meat samples possessed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Compared with to aldrin, the concentration of dieldrin was lower in the control sample (4.84%), as well as in the cooked and baked samples (4.43 and 5.28%, respectively). One explanation could be the possible oxidation of aldrin to dieldrin, as already reported in the literature [10,22,23]. The lowest levels of endrin aldehyde were determined for the pasteurization combined with the warm smoking treatment (4.65%).…”
Section: Organochlorine Pesticides Weight Variability During Applied supporting
confidence: 61%
See 1 more Smart Citation
“…Compared with to aldrin, the concentration of dieldrin was lower in the control sample (4.84%), as well as in the cooked and baked samples (4.43 and 5.28%, respectively). One explanation could be the possible oxidation of aldrin to dieldrin, as already reported in the literature [10,22,23]. The lowest levels of endrin aldehyde were determined for the pasteurization combined with the warm smoking treatment (4.65%).…”
Section: Organochlorine Pesticides Weight Variability During Applied supporting
confidence: 61%
“…Therefore, it is important to reduce levels of OCPs in food of animal origin. Studies on the influence of thermal processing of foods contaminated with OCP residues have showed this treatment as being the determining factor for their significant decrease through food processing [5][6][7][8][9][10][11]. Thus, thermal treatments, such as frying, baking, grilled, boiling and microwave cooking were the best options to reduce the pesticide load in raw meat [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to meat, Sengupta and others () suggested that autoclaving meat, which is cooking meat under pressure, is preferable to baking it, because the former confers a greater degree of steam penetration, which is more efficient at reducing the concentrations of total HCH, total DDT, endosulfans, dimethoate, and malathion in chicken, cow, and goat meat. Cooked chicken meat shows a higher reduction in the levels of pesticides comparing with those in cooked cow and goat meat.…”
Section: Impact Of Cooking On Agrochemical Contaminants Present In Mementioning
confidence: 99%
“…Almost every person is or has been exposed to OP insecticides in their home or work environment or as trace dietary contaminants (Casida and Quistad 2004;Sengupta et al 2010). Children of pesticide workers may be exposed through occupational sources (storage of working equipment in the house, contamination of clothes, etc.).…”
Section: Introductionmentioning
confidence: 99%